Vocal correlates of affective states - Yanushevskaya, Irena (Trinity College (Dublin, Ireland). Centre for Language and Communication Studies, 2010)
This thesis explores the mapping of voice quality to affect. Three studies have been conducted. The principal study of this thesis is a cross-language study, aimed at clarifying how variations in voice quality (in synthesised stimuli) can evoke different affective colouring for subjects from four different language backgrounds: Hiberno-English, Russian, Spanish and Japanese. This study furthermore addresses, by including major fo differences in some stimuli, some aspects of the role of fo in affect cueing. It was of interest to ascertain (1) whether voice quality cues become more effective when major fo perturbations are included, (2) what is the contribution of dynamic fo contour when voice quality is kept modal, (3) whether and to what extent the stimuli incorporating these voice quality and fo variations impart similar/different affective colouring to the listeners from different language groups. In the listening tests, the listeners were presented with three types of stimuli: (1) ‘VQ only’ stimuli with distinct voice quality variations (whispery, breathy, lax-creaky, tense and modal); (2) 'fo only’ stimuli in all of which modal voice quality was combined with affect-related fo variations (boredom, sadness, joy, indignation, fear, and neutral); (3) ‘VQ + fo' stimuli in which distinct non- modal voice qualities were combined with certain affect-related fo contours. The strength of affective content of each stimulus was assessed for a number of affective labels; apologetic- indignant, bored-interested, intimate-formal, relaxed-stressed, sad-happy and scared-fearless
Keywords: Language and Communication Studies, Ph.D.; Ph.D. Trinity College Dublin